Optimization Design of Steering System of Double Cross Shaft Universal Joint Driving - Pan Yu; He Yunfeng; He Zhibing; Wu Chudong (Jixie chuandong)
Aiming at the problem of automobile steering design with a double cross shaft universal joint transmission,by spatial layout design to achieve a smooth speed output shaft is studied.Taking a vehicle steering system as an example,the dynamics model of ADAMS/view double cross universal joint is established,with the output shaft of the speed fluctuation rate as the optimization objective,optimization design of the parameters can be changed in the system is carried out,finally,the ideal steering hard point layout scheme is got.